2013
DOI: 10.1002/lt.23703
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for hepatitis B liver disease and concomitant hepatocellular carcinoma in the United States With hepatitis B immunoglobulin and nucleoside/nucleotide analogues

Abstract: 7Methodist Hospital, Houston, TX Reinfection with hepatitis B virus (HBV) after liver transplantation (LT) may favor the recurrence of hepatocellular carcinoma (HCC), and combination therapy with hepatitis B immunoglobulin (HBIG) and nucleoside/nucleotide analogues may reduce HBV recurrence after LT. To test associations between HBV, HCC, and survival, we performed a retrospective chart review of patients undergoing LT for HBV between January 1985 and December 2010 at 7 US transplant centers. After we divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
(43 reference statements)
1
20
0
Order By: Relevance
“…Although HBIG combined with NUCs (mainly LAM) after LT has been the most effective prophylaxis regimen for HBV recurrence in clinical practice until now, HBV recurrence was associated with graft loss, HCC recurrence, and significantly decreased survival rate in LT recipients [8,9]. Furthermore, recent studies have found that high preoperative HBV DNA load (>10 5 copies/ml), HBV mutation, and HCC in the explant liver were independent risk factors for HBV recurrence following LT [10].…”
mentioning
confidence: 99%
“…Although HBIG combined with NUCs (mainly LAM) after LT has been the most effective prophylaxis regimen for HBV recurrence in clinical practice until now, HBV recurrence was associated with graft loss, HCC recurrence, and significantly decreased survival rate in LT recipients [8,9]. Furthermore, recent studies have found that high preoperative HBV DNA load (>10 5 copies/ml), HBV mutation, and HCC in the explant liver were independent risk factors for HBV recurrence following LT [10].…”
mentioning
confidence: 99%
“…Histopathologic examination revealed poorly differentiated HCC around 9 × 7 × 7 cm, grade ¾ without lymphovascular invasion. Hepatitis B immunoglobulin (HBIG) and entecavir were taken for HBV treatment and HBV DNA subsequently turned negative after that [10]. Rapamycin-based post-transplant immunoprophylaxis without steroids was subsequently initiated after transplantation.…”
Section: Case Presentationmentioning
confidence: 99%
“…This mandatory duration of abstinence is a matter of debate because the 6-mo threshold has shown to be insufficient for predicting long-term graft and patient survival (Rice and Lucey 2013). Although uncontrolled systemic infections, which exclude patient survival under immunosuppression, and AIDS-defining symptoms in HIV patients are absolute contraindications, the possibility of performing a liver transplantation in patients diagnosed with infections such as HBV and HIV and controllable local infections must be assessed for each individual patient (Grossi 2003;Tavio et al 2011;Campsen et al 2013). Further absolute contraindications for liver transplantation are life-limiting medical conditions such as advanced cadiovascular, pulmonary, or neurologic disorders; intrahepatic CCA; hepatic metastases other than neuroendocrine metastases in selected patients; and extrahepatic malignancy (see also Lakkis and Lechler 2013).…”
Section: Contraindications For Liver Transplantationmentioning
confidence: 99%